Entrepreneurship education in the Kingdom of Saudi Arabia in the light of Malaysia's experience - Al-Mutairi, Alaa Rabeh (Journal of Educational and Psychological Sciences, 2021)
This research aims to benefit from Malaysia's experience in the application of entrepreneurship education in the Kingdom of Saudi Arabia in light of the forces and factors affecting it, and to achieve this goal, the descriptive comparative approach was chosen for its consistency with the nature of the current research and its procedures, through which entrepreneurship education in schools is identified Public education in the Kingdom of Saudi Arabia, and analyzing the reality of the problem in light of the cultural forces and factors that explain it and stand behind it, to come up with general rules and results that can be generalized, and then reach evidence of benefit for the application of entrepreneurship education in the Kingdom of Saudi Arabia in light of the experience of the State of Malaysia and in line with the culture of society The research has reached a set of results, the most important of which are: Saudi Arabia has been concerned with developing human resources to enable the various elements of society to increase their productive contribution to diversifying sources of national income and to achieve and build national economic development, Saudi Arabia has also recently made extensive efforts in the field of entrepreneurship education, by introducing some Topics concerned with providing the learner with labor market skills and entrepreneurship in some secondary school courses, except for teaching students Entrepreneurial skills and their preparation at an early age starting from elementary school creates their own opportunities for the future to enter the field of entrepreneurship, In light of these results the researcher recommends the need to include curricula for teaching entrepreneurship in the general education stages.
Keywords: Entrepreneurship education; Entrepreneurship; Saudi Arabia; Malaysia